PAH and PCB body-burdens in epibenthic deep-sea invertebrates from the northern Gulf of Mexico. (January 2021) - Lawson, M. Chase; Cullen, Joshua A.; Nunnally, Clifton C.; Rowe, Gilbert T.; Hala, David N.
Abstract: There is a paucity of information on the levels of PAHs and PCBs in the deep-sea (≥200 m). In this study, the body-burdens of 16 PAHs and 29 PCBs were measured in: Actinaria (sea anemones), Holothuroidea (sea cucumber), Pennatulacea (sea pens), and Crinoidea (sea lilies) in the deep Gulf of Mexico. All epibenthic species were collected at depths of approximately 2000 m. The PAH and PCB congener profile displayed a similar pattern of bioaccumulation across all four taxa. The high molecular weight PAH, dibenz[ a, h ]anthracene, was the most abundant PAH in all organisms, ranging from 36 to 53% of sum total PAHs. PCBs 101 and 138 exhibited the highest levels at 20–25% of total congener concentrations in all taxa. The exposure to PAHs and PCBs is likely attributed to contaminated particulate organic matter that is consumed by the deposit and filter feeding epibenthic megafauna sampled in this study. Highlights: Body-burdens of PAH and PCB congeners were quantified in four taxa of epibenthic deep-sea megafauna. Three congeners made up the majority of total PAHs in all four taxa: dibenz[ a, h ]anthracene, benzo[ a ]pyrene, and acenaphthene. The primary polychlorinated biphenyls found in the deep-sea megafauna were congeners 101 and 138. This study shows that deep-sea invertebrates have the propensity to bioaccumulate relatively high levels of PAHs and PCBs